Interpretations of the impact of cross-field drifts on divertor flows in DIII-D with UEDGE. (August 2017) - Jaervinen, A.E.; Allen, S.L.; Groth, M.; McLean, A.G.; Rognlien, T.D.; Samuell, C.M.; Briesemeister, A.; Fenstermacher, M.; Hill, D.N.; Leonard, A.W.; Porter, G.D.
Highlights: UEDGE simulations indicate that the toroidal C 2+ flow velocities in the divertor plasmas are mainly entrained within 30% to the background deuterium flow in both L- and H-mode plasmas in the plasma region where the CIII 465 nm emission is measured. The simulations indicate that in L-mode plasmas, the poloidal particle flows in the divertor are dominated by ionization driven flows, whereas radial particle fluxes are dominate ExB drifts. The simulations indicate that in H-mode plasmas, both radial and poloidal particle flows in the steep gradient region next to the separatrix are dominated by ExB flows. Abstract: Simulations using the multi-fluid code UEDGE indicates that, in low confinement (L-mode) plasmas in DIII-D, poloidal projection of the ionization driven flows dominate poloidal particle flows in the divertor near the divertor plates, whereasE × B drift flows dominate the radial particle flows. In contrast, in high confinement (H-mode) conditionsE × B drift flows dominate both poloidal and radial particle flows in the divertor in the vicinity of the strong gradient region near the separatrix. UEDGE indicates that the toroidal C 2+ flow velocities in the divertor plasmas are mainly entrained within 30% to the background deuterium flow in both L- and H-mode plasmas in the plasma region where the CIII 465 nm emission is measured. Therefore, UEDGE indicates that the Doppler Coherence Imaging Spectroscopy (CIS), measuring the toroidal velocity of the C 2+ ions, can provide insight to the deuterium flows in the divertor. Parallel-to-B velocity dominates the toroidal divertor flow; direct drift impact being less than 1%. Toroidal divertor flow is predicted to reverse when the magnetic field is reversed. This is explained by the parallel-B flow towards the nearest divertor plate corresponding to opposite toroidal directions in opposite toroidal field configurations.